Liberia : Report on Post-Conflict Economic Conditions and Economic Program for 2004/05. (IMF Staff Country Reports; Country Report ;, 2004)
This report reviews Liberia's Post-Conflict Economic Conditions and Economic Program for 2004-05. The economy of Liberia is recovering, following a sharp contraction in the second half of 2003, as a result of increasing donor support and the revival of associated manufacturing and services activities. Despite political and capacity constraints, the economic program through June 2004 was implemented successfully. The monetary program for 2004-05 aims at a broadly stable exchange rate, while accommodating a further rebound in the demand for local currency.